Effects of track and rolling stock interaction on track condition and maintenance - Oleg A. Suslov (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. A number of railway lines in Russia experience increased traffic volume. The lines with the fastest annual growth are the Eastern Polygon, Transsib and BAM sections. Higher volumes of trailing load, especially in limited trafficcarrying capacity, entail longer and heavier trains and higher axle loads, which puts more strain on the existing railway infrastructure, especially the tracks. This intensifies the interaction in the wheel — rail system, further increasing track load and damage rates. This paper is intended to identify the correlation between operational factors and track load indicators.Materials and Methods. The study of the actual damage rate on the network and the Eastern Polygon sections involved automatic devices collecting wheel — rail interaction data for several months and determined the laws and parameters of their distribution.Results. The analysis of distribution parameters showed large variation (45–55% for average values and up to 300 % for dispersions). A similar variation was obtained for the accumulated damage and resource exhaustion rates on the investigated track sections. The work also reveals a high dependence of damage rate (from 40% and above) on the  dynamic qualities of the rolling stock determined by its design and condition. Discussion and Conclusion. Structural and maintenance solutions for tracks with particularly high usage require constant monitoring and analysing of the loads in the wheel — rail system. This approach would improve track design and maintenance based on the operational characteristics of specific lines for safer traffic and more efficient track maintenance and repair costs.